Desertion and failure, according to university students, taking General Mathematics - Hidalgo Mora, Randall (2019)
This article describes desertion and failure in the first course of Mathematics at the National University of Costa Rica from the students’ point of view and draws general lines regarding possible causes. This course has high desertion and failure rates that affect academic progress, as it has both, personal and social implications in terms of student and family expectations: emotional effects due to the discrepancy between the students’ aspirations and their achievements; and economic consequences for the university system. This research surveyed the whole population of students enrolled in the first and second school year of 2017. Students filled out a questionnaire via email addressing general aspects and possible causes of desertion and failure. The analysis showed a high desertion rate regardless of the school period; the highest percentage of approval was in the second cycle, especially in women, possibly associated with a learning process or adaptation to university life. Students that constitute the lower percentage of approval and higher percentage of failure come from public schools, which happens to make up the majority of the university population. Students point to low academic performance, previous knowledge, and study habits as the causes of desertion. It is necessary to generate institutional policies that reduce the desertion and disapproval, specifically in courses of first entrance to the university, and therefore shorten graduation times and optimize institutional resources.